Refractory postoperative Staphylococcus hominis bacteremia in a patient with an ACTH-producing pancreatic neuroendocrine neoplasm: a case report - Ryuta Muraki; Yoshifumi Morita; Kyota Tatsuta; Shinya Ida; Ryo Kitajima; Amane Hirotsu; Makoto Takeda; Hirotoshi Kikuchi; Yoshihiro Hiramatsu; Atsuko Fukazawa; Go Kuroda; Keisuke Kakizawa; et al. (Surgical Case Reports)
Abstract Background Staphylococcus hominis (S. hominis) is an opportunistic pathogen that is often highly resistant to antibiotics and is difficult to treat. In patients diagnosed with an adrenocorticotropic hormone (ACTH)-producing tumor that compromises the immune system due to hypercortisolemia, cancer treatment and infection control should be considered simultaneously. This report presents a case of refractory postoperative S. hominis bacteremia requiring the prolonged administration of several antibiotics in a patient with an ACTH-producing pancreatic neuroendocrine neoplasm (pNEN). Case presentation A 35-year-old man visited a neighboring hospital for a thorough examination after experiencing weight gain and lower limb weakness for several months. Enhanced computed tomography revealed a pancreatic tail tumor and bilateral adrenal enlargement. Elevated plasma ACTH and serum cortisol were noted. Biopsy under endoscopic ultrasonography revealed the tumor as an ACTH-producing pNEN. The patient was transferred to our hospital for further treatment. Pneumocystis pneumonia was noted and treated with sulfamethoxazole and adjunctive glucocorticoids. Hypercortisolism was controlled with metyrapone and trilostane. Somatostatin receptor scintigraphy and ethoxybenzyl magnetic resonance imaging detected other lesions in the pancreatic head. A total pancreatectomy was performed given that the lesions were found in both the pancreatic head and tail. Plasma ACTH and serum cortisol levels decreased immediately after the resection. Pathological examination revealed that the pancreatic tail tumor was NEN G2 and T3N1aM0 Stage IIB and the pancreatic head lesions were SSTR-positive hyperplasia of the islet of Langerhans cells. On postoperative day 11, catheter-associated bacteremia occurred. Initially, meropenem hydrate and vancomycin hydrochloride were administered empirically. S. hominis was identified and appeared sensitive to these antibiotics according to susceptibility testing. However, S. hominis was repeatedly positive in blood cultures for more than one month, despite treatment with several antibiotics. Eventually, with the combined use of three antibiotics (meropenem hydrate, vancomycin hydrochloride, and clindamycin phosphate) for more than 3 weeks, the S. hominis-associated bacteremia improved. He was discharged 79 days after surgery. Conclusions Our patient with an ACTH-producing pNEN was immunocompromised and needed meticulous attention for infectious complications even after successful tumor removal. Specifically, S. hominis bacteremia in such patients demands intensive treatments, such as with combinational antibiotics.